PENGARUH INFLASI, BI RATE DAN KURS TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA (An-Nisbah: Jurnal Ekonomi Syariah, 2014)
This study aims to determine the effect of the infation rate, interest rate (BI rate) and the rate of proftability of Islamic banks in Indonesia. The object of the research includes 11 Islamic banks and 24 Islamic business units. Proftability of Islamic banks is the dependent variables, while infation, the BI rate and the exchange rate is an independent variables. The analysis technique used in this study is multiple linear regression. The results showed that the rate of infation and exchange rate variables have a signifcant impact on the proftability of Islamic banks. While the BI rate variable has no signifcant effect.Keywords: Infation, the BI rate, exchange rate, Islamic Bank Proftability